Pengaruh penggunaan e-money, BI-rate dan jumlah uang beredar terhadap pertumbuhan ekonomi di Indonesia - Samnia Putri, Novita; Nurjanah, Rahma; Nurhayani, Nurhayani (e-Journal Perdagangan Industri dan Moneter, 2024)
This research aims to determine and analyze the development of e-money, BI-rate, money supply and economic growth in Indonesia as well as to determine and analyze the influence of e-money, BI-rate and money supply on economic growth in Indonesia. The analytical method in this research is descriptive analysis and quantitative analysis. The quantitative analysis tool uses E-views with multiple linear regression methods. Based on the results and discussion using the multiple linear regression method, it is known that the Economic Growth variable experiences quite significant fluctuations every quarter and has an average development of 4.02%, the E-Money variable has an average development of 20.67%, the BI variable -Rate has an average development of 5.25%, and the money supply variable has an average development of 18.55%. Multiple linear regression shows the results that the E-Money and BI-Rate variables have a significant effect on the economic growth variable, while the Money Supply variable has no effect on the Economic Growth variable in Indonesia.